2013
DOI: 10.5296/jbls.v4i2.3144
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides and Its Effects on Health Status of Workers in Swat, Khyber Pakhtunkhwa, Pakistan

Abstract: Pesticides are a large and diverse group of chemicals used to kill and eradicate rodents, fungi, insects, and weeds. The present study was designed to check the effect of pesticides on liver as well as kidney function of the workers engaged in occupations in which there is persistent exposure to pesticides, (dealers, gardeners and owners of gardens), and to check the prevalence of hepatitis in these workers indistrict Swat, Khyber Pakhtunkhwa, Pakistan. Blood samples ISSN 2157-6076 2013 www.macrothink.org/jbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Similarly, an increase in the levels of Mid %, Gran %, MCV and WBC has also been reported by Dunstan et al (1996), which again justify our findings. Khan et al (2013) observations are also in consistency with the present finding who revealed a significant increase in the count of HGB and RBCs upon exposure of the individuals to pesticides. No significant differences were noted in the MPV count in response to pesticides exposure of the studied field workers.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, an increase in the levels of Mid %, Gran %, MCV and WBC has also been reported by Dunstan et al (1996), which again justify our findings. Khan et al (2013) observations are also in consistency with the present finding who revealed a significant increase in the count of HGB and RBCs upon exposure of the individuals to pesticides. No significant differences were noted in the MPV count in response to pesticides exposure of the studied field workers.…”
Section: Discussionsupporting
confidence: 94%
“…However, some preliminary studies have indicated that occupational exposure to pesticides can significantly affect the blood constituents (Khan et al, 2013). Similarly, several studies have been conducted in animals which report that pesticides alter the haematology of animals (Khatun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[4,6] Pesticides exposures of agricultural workers were major occurred while were contact on mixing, loading, and spraying pesticides in farming and orchard area, and the rate of exposure may be several times of proportion in agriculturalist higher than in general people. [2,5,7] Intensively, pesticide usage was lead high accumulation of toxic residues in environment (such as in soil, sediment, and water resources) and may spread to ecosystem (including aquatic animals, livestock, and agricultural products). The top of the food chain is humans; thus, pesticides are also contained in human body and hence made harmful health outcome.…”
Section: Original Articlementioning
confidence: 99%
“…50 Similar trend was also reported by a study carried out in Egypt where significant incidence of health related problems were reported in agricultural community. 51,52,53 Another study also pointed out that the incidence of pesticide exposure increased among workers who had not followed instructions / guidelines for proper handling of pesticides. 15,54,3 Significantly altered biochemical responses in the populations under investigation with more number of years (< 10) and particularly that BChE levels (Table 4) support the idea that the toxicity of insecticide increases with the passage of time.…”
Section: Discussionmentioning
confidence: 99%